Agronomic assessment of vine segment and variety influence on the production of sweet potato (Ipomoea batatas) (Agriculture, Food, and Natural Resources Journal, 2025)
Sweet potato (Ipomoea batatas L.) plays a vital role in enhancing food security in Nigeria, yet many farmers continue to propagate it using vine cuttings without regard to the specific segment—basal, middle, or apical. To evaluate the impact of vine segment and variety on growth and yield, a field experiment was conducted at the Osun State Water Mini Scheme, Ejigbo, Nigeria, on an experimental plot measuring 810 m². The study was laid out in a randomized complete block design in a 3 ×4 factorial arrangement with three replications. Treatments included three vine cutting positions (basal, middle, apical) and four sweet potato varieties (TIS87/0087, 440261, Modern Delight, and King J). Results revealed that variety had a significant effect (P < 0.05) on key parameters such as vine length, tuber weight per plant, number of tubers per plant, tuber weight per plot, and total yield (tons/ha). Among the varieties, TIS87/0087 produced the highest yield (3.03 tons/ha), followed closely by 440216 (3.10 tons/ha), while Mother's Delight (2.06 tons/ha) and King J (2.18 tons/ha) recorded the lowest. The vine segment also significantly influenced growth and yield. Apical cuttings (tip) consistently outperformed both middle and basal segments, with the highest vine length (36.93 cm in Week 1) and yield of 3.04 tons/ha, compared to 2.36 and 2.38 tons/ha for middle and base cuttings, respectively.
Keywords: Osun State; Variety performance; Vine segment; Yield optimization